2017
DOI: 10.4490/algae.2017.32.5.24
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of copper on the freshwater alga Closterium ehrenbergii Meneghini (Conjugatophyceae) and its potential use in toxicity assessments

Abstract: Although green algae of the genus Closterium are considered ideal models for testing toxicity in aquatic ecosystems, little data about the effects of toxicity on these algal species is currently available. Here, Closterium ehrenbergii was used to assess the acute toxicity of copper (Cu). The median effective concentration (EC 50) of copper sulfate based on a dose response curve was 0.202 mg L-1 , and reductions in photosynthetic efficiency (F v / F m ratio) of cells were observed in cultures exposed to Cu for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In details, the effect of different concentrations of CuCl 2 presented shows that decrease of the auto‐fluorescence (red color) is accompanied with the increase of the production of ROS (green color; Figure A), indicating that CuCl 2 could trigger oxidative stress, even at lower concentrations. The observed effect of CuCl 2 matches with previous reports on C. ehrenbergii and also other species, about the increase ROS production during oxidative stress . In addition, the effect of K 2 Cr 2 O 7 , at 2 and 4 mg/L concentrations, and the increase of fluorescence (ROS production) was proportional to the increasing concentrations.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…In details, the effect of different concentrations of CuCl 2 presented shows that decrease of the auto‐fluorescence (red color) is accompanied with the increase of the production of ROS (green color; Figure A), indicating that CuCl 2 could trigger oxidative stress, even at lower concentrations. The observed effect of CuCl 2 matches with previous reports on C. ehrenbergii and also other species, about the increase ROS production during oxidative stress . In addition, the effect of K 2 Cr 2 O 7 , at 2 and 4 mg/L concentrations, and the increase of fluorescence (ROS production) was proportional to the increasing concentrations.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, increasing concentration of potassium dichromate has shown to be inducing a general decline in cell densities in the green alga Pseudokirchneriella subcapitata . Moreover, recent study by Wang et al on the effect of copper on C. ehrenbergii showed that F v /F m was considerably affected by copper toxicity and also declined with increasing copper concentration and exposure time, indicating that chlorophyll content and/or photosynthetic electron transport might be inhibited by exposure to the metal …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations